2018
DOI: 10.1002/adom.201701119
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Plasmonic Antenna Enhanced Upconversion and Its Application in Flexible Fingerprint Identification

Abstract: photons can be efficiently converted into electron oscillations in plasmonic nanostructures. [1] The use of plasmonic antennas could substantially enhance the efficiency of many optoelectronic devices by utilizing long-wavelength light beyond the visible region, which accounts for more than a half of the total solar energy. [2] For example, Xiong and co-workers recently developed a flexible near-infrared (NIR) photovoltaic device whose external quantum efficiency (at ≈800 nm) was improved from 24.2% to 38.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“… eUCQY [ 141 ] LiYF 4 : Er 3+ ,Yb 3+ Powder L: ~2.0 µm (Octahedral) - *>0.1 980 (*Gauss) - 2.1 (*350-750) - A, B, C?, D?, F?, H?, I, J C? eUCQY [ 142 ] SrF 2 : (14.2%)Er 3+ Powder -(*Varied) - *>0.1 980 (*Gauss) 25 63 0.17 (*350-700) 0.28 (*350-700) 6.8 x10 −3 4.4 x10 −3 A, B, C?, D?, F, H?, I, J C? eUCQY [ 143 ] SrF 2 : (2%)Yb 3+ ,(2%)Er 3+ Powder 100-300 nm (Spherical and pseudo-cubic) - *>0.1 980 (*Gauss) 10 2.8 (*400-900) 0.28 A, B, C?, D?, F, H?, I, J C?…”
Section: Reviewing the Ucqy Reporting And Measurement Techniques In The Literaturementioning
confidence: 99%
“… eUCQY [ 141 ] LiYF 4 : Er 3+ ,Yb 3+ Powder L: ~2.0 µm (Octahedral) - *>0.1 980 (*Gauss) - 2.1 (*350-750) - A, B, C?, D?, F?, H?, I, J C? eUCQY [ 142 ] SrF 2 : (14.2%)Er 3+ Powder -(*Varied) - *>0.1 980 (*Gauss) 25 63 0.17 (*350-700) 0.28 (*350-700) 6.8 x10 −3 4.4 x10 −3 A, B, C?, D?, F, H?, I, J C? eUCQY [ 143 ] SrF 2 : (2%)Yb 3+ ,(2%)Er 3+ Powder 100-300 nm (Spherical and pseudo-cubic) - *>0.1 980 (*Gauss) 10 2.8 (*400-900) 0.28 A, B, C?, D?, F, H?, I, J C?…”
Section: Reviewing the Ucqy Reporting And Measurement Techniques In The Literaturementioning
confidence: 99%
“…Experimental results have shown that a maximum of up to tenfold blue upconversion luminescence enhancement is achieved at the optimal 3 nm working distance between InNCs and UCNPs. This is reasonable since the surface plasmon of Au or Ag resonances with visible light (520–660 nm) at longer wavelengths, which can travel longer distance (>10 nm) while that of InNCs is trapped within a smaller range due to the short surface plasmon wavelength, characterized by the typical UV absorption at 265 nm …”
Section: Resultsmentioning
confidence: 94%
“…Among them, surface plasmon resonance (SPR) has proved to be a facile and efficient method for enhancing upconversion emissions, by resonating with either the excitation or emission process . For example, since the first demonstration that coating upconversion nanoparticles with gold nanocrystals or nanoshells can drastically enhance upconversion luminescence, Ag nanostructures and Au nanorods have also been utilized for this purpose and the enhancement factor keeps increasing . However, this strategy usually enhances green and red upconversion emissions (i.e., 520–660 nm) since the SPR bands of Au and Ag nanostructures usually locate within the visible to near infrared range, which is not compatible for enhancing short‐wavelength luminescence such as blue or UV emission.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports reveal that the upconversion luminescence can be efficiently enhanced by coupling UCNPs with plasmonic metal nanostructures . Due to the emission and absorption band match between the UCNPs and surface plasmon in grating nanohole array, nanoparticle and photonics crystal, the upconversion intensity can be dramatically enhanced by several to thousand folds . Lu et al reported a nanosilver grating which couples efficiently with UCNPs and got an enhancement factor of 16 for the green emission under the excitation of 1 kW cm −2 .…”
Section: Introductionmentioning
confidence: 99%